Understanding multilingualism and interculturalism from an Ecuadorian perspective - Rodas, Fabián Darío; Santillán, Juan José (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
The phenomenon of globalization has brought the world closer and has changed the way we live and communicate. Therefore, without the physical barriers that separate countries, people have found new ways to be in touch with the different inhabitants of the world village. In this context, people have seen the need to learn new languages, which takes one to the fascinating field of multilingualism. However, being able to communicate in many languages is not an isolated process, since it is closely related to culture; this fact leads us to the area of interculturalism, that is, being aware of the other – of the different one – being able to understand and feel how the other feels. This paper explores the concepts of multilingualism and interculturalism, along with some considerations of the Ecuadorian context.